2005
DOI: 10.1016/j.ccr.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

De novo carcinogenesis promoted by chronic inflammation is B lymphocyte dependent

Abstract: Chronic inflammation predisposes tissue to cancer development; however, regulatory mechanisms underlying recruitment of innate leukocytes toward developing neoplasms are obscure. We report that genetic elimination of mature T and B lymphocytes in a transgenic mouse model of inflammation-associated de novo epithelial carcinogenesis, e.g., K14-HPV16 mice, limits neoplastic progression to development of epithelial hyperplasias that fail to recruit innate immune cells. Adoptive transfer of B lymphocytes or serum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

19
548
3
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 736 publications
(584 citation statements)
references
References 53 publications
19
548
3
14
Order By: Relevance
“…Adoptive transfer of B lymphocytes or serum into B-cell-deficient/HPV16 mice restored innate immune cell infiltration into premalignant tissue and reinstated necessary parameters for full malignancy (e.g. chronic inflammation, angiogenic vasculature and hyperproliferative epidermis) [11]. These findings suggest a model in which B lymphocytes are crucial in establishing chronic inflammation associated with de novo carcinogenesis; however, as B cells do not infiltrate the precancerous tissues, it was suggested that infiltration and functions of innate immune cells must be orchestrated remotely [12], suggesting that lymphocyte-derived cytokines and/or antibodies may drive the cancer-promoting inflammation.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Adoptive transfer of B lymphocytes or serum into B-cell-deficient/HPV16 mice restored innate immune cell infiltration into premalignant tissue and reinstated necessary parameters for full malignancy (e.g. chronic inflammation, angiogenic vasculature and hyperproliferative epidermis) [11]. These findings suggest a model in which B lymphocytes are crucial in establishing chronic inflammation associated with de novo carcinogenesis; however, as B cells do not infiltrate the precancerous tissues, it was suggested that infiltration and functions of innate immune cells must be orchestrated remotely [12], suggesting that lymphocyte-derived cytokines and/or antibodies may drive the cancer-promoting inflammation.…”
mentioning
confidence: 95%
“…A first original report on B cells and cancer progression, in a transgenic mouse model of inflammation-associated cancer (HPV16 mice), demonstrated the importance of B cells in de novo epithelial carcinogenesis [11]. Adoptive transfer of B lymphocytes or serum into B-cell-deficient/HPV16 mice restored innate immune cell infiltration into premalignant tissue and reinstated necessary parameters for full malignancy (e.g.…”
mentioning
confidence: 99%
“…7 Progression of human papillomavirus type 16 E6/E7-driven squamous carcinogenesis in transgenic mice is significantly diminished in the absence of B cells. 8,9 In this preclinical tumor model, promotion of the early steps of carcinogenesis is achieved through deposition of IgG autoantibody in the neoplastic parenchyma and immune complex/FcgR ligation of mast cells and macrophages, eventually fostering proangiogenic and immunosuppressive gene expression programs. 8,9 Similarly, skin chemical carcinogenesis by two-stage application of the DNA damaging agent DMBA and the tumor promoter TPA occurs more rapidly in B-cell-proficient mice than in B-celldeficient mice.…”
mentioning
confidence: 99%
“…8,9 In this preclinical tumor model, promotion of the early steps of carcinogenesis is achieved through deposition of IgG autoantibody in the neoplastic parenchyma and immune complex/FcgR ligation of mast cells and macrophages, eventually fostering proangiogenic and immunosuppressive gene expression programs. 8,9 Similarly, skin chemical carcinogenesis by two-stage application of the DNA damaging agent DMBA and the tumor promoter TPA occurs more rapidly in B-cell-proficient mice than in B-celldeficient mice. 10 As a possibility, B cells may modulate myeloid cell phenotypes through the secretion of IL-10 and TNFa, thereby accelerating tumor progression.…”
mentioning
confidence: 99%
“…This scenario is now changed as some in vitro studies have made clear that M1 macrophages are only cytotoxic to tumor cells but not to normal cells and, therefore, these M1 cells help in the early eradication of neotrasfromed cells [48][49][50][51][52][53]. Another way by which M1 macrophages exert their antitumor activity is through their antagonistic action on tumor-promoting action of TAMs, myeloid-derived suppressor cells (MDSCs), M2 macrophages, regulatory macrophages, and immature myeloid cells (i.e., all these cells suppress adaptive tumor-specific immune response and promote tumor growth and development) [54][55][56][57][58][59]. The exact role of macrophages in early stages of cancer is still controversial and yet to be determined.…”
Section: Classically Activated Macrophages (M1 Macrophages)mentioning
confidence: 99%